Azithromycin Inhibits Mucus Hypersecretion from Airway Epithelial Cells - Takeshi Shimizu; Shino Shimizu (Mediators of Inflammation)
To examine the in vivo effects of the 15-member macrolide, azithromycin (AZM), on mucus hypersecretion, we induced hypertrophic and metaplastic changes of goblet cells in rat nasal epithelium by intranasal instillation of ovalbumin (OVA) in OVA-sensitized rats, or by intranasal lipopolysaccharides (LPS) instillation. Oral administration of AZM (5–10 mg/kg) or clarithromycin (CAM, 5–10 mg/kg) significantly inhibited OVA- and LPS-induced mucus production, whereas josamycin (JM) or ampicillin (ABPC) showed no effect. In vitro effects of AZM on airway epithelial cells were examined using NCI-H292 cells and human nasal epithelial cells cultured in air-liquid interface. Mucus secretion was evaluated by enzyme-linked immunosorbent assay using an anti-MUC5AC monoclonal antibody. AZM or CAM significantly inhibited tumor necrosis factor-α (TNF-α) (20 ng/mL)-induced MUC5AC secretion from NCI-H292 cells at 10−6–10−7 M, whereas JM or ABPC showed no effect. AZM significantly inhibited TNF-𝛼 (20 ng/mL)-induced MUC5AC secretion from human nasal epithelial cells at 10−4 M. MUC5AC mRNA expression was also significantly inhibited. These results indicate that the 15-member macrolide, AZM, exerts direct inhibitory effects on mucus secretion from airway epithelial cells and that it may be useful for the treatment of mucus hypersecretion caused by allergic inflammation and LPS stimulation.